Spatial-temporal variations in blue and green water resources, water footprints and water scarcities in a large river basin: A case for the Yellow River basin - Xie, Pengxuan; Zhuo, La; Yang, Xi; Huang, Hongrong; Gao, Xuerui; Wu, Pute (Journal of hydrology (Amsterdam), 2020)
[Display omitted] •Blue and green water resources, footprints and scarcities were quantified.•Effects of irrigation on blue and green water resources were considered.•Middle reaches faced both blue and green water scarcities at least 3 months a year. Blue water (surface and ground water) and green water (water stored in unsaturated soil layer and canopy evapotranspiration from rainfall) are the two sources of water generated from precipitation and communicating vessels that define the limits of water resources (WRs) for both human activities and ecosystems. However, the blue and green evapotranspiration in irrigated fields and their contribution to blue and green water flows have not been identified in studies conducted on blue and green WRs. In addition, information on intra-annual variations in green water footprints (WFs) and water scarcities is limited. In particular, there is a lack of information on water consumption obtained from hydrological model-based blue and green water assessments at the basin scales. This study quantified, taking the Yellow River Basin (YRB) over 2010–2018 as the study case, the inter- and intra-annual variations in blue and green WRs, WFs and water scarcities at sub-basin levels. WRs and WFs were simulated using the Soil and Water Assessment Tool (SWAT) model. The results revealed that the annual average blue and green WRs of the YRB were 119.33 × 109 m3 yr−1 and 296.94 × 109 m3 yr−1, respectively, over the study period. The blue and green WFs of the crops in the middle reach were significantly larger than those of the crops in the upper and lower reaches. There were visible spatial heterogeneities in water scarcities across the basin. Several areas in the middle reaches were subject to both blue and green water scarcities (at least modest level) for a minimum of three months a year. Furthermore, the norther region of the YRB was subject to significant and severe blue water scarcity for the whole year.